Electric vehicle charging system - Ren, Jiasheng (2013)
Singapore being a clean and green city, each individual is willing to take more responsibility for their direct contribution to greenhouse gas emissions. Electrical Vehicle (EV) no longer have to face consumer fear of complete novelty. This growing interest in electric vehicles concepts for private, public and utility services across the world has certainly encouraged many companies and organisations to push various other technologies associated with electric vehicles. The electric vehicle charging system is a new technology that helps users monitor thier electric vehicle charge status and notify users when charge is complete. LabVIEW is used as the main software programming language in creating the GUI display in this project.